The necessary discipline of "professional orientation" in teacher training for the 21st century - Gilsenir Maria Prevelato de Almeida Dátilo (Universidade Estadual Paulista Júlio de Mesquita Filho, 2016)
The objective of this article is to demonstrate the results of a survey conducted by the author and students of Pedagogy UNESP Marilia. Objectives: 1) verify the importance of Career Guidance (OP) in the course of teacher training, the role the teacher can play in assisting prospective students in choosing a profession 2) to investigate what it means for your student career choice, 3) identify the design that have on the subject work, 4) provide activities that encourage self-awareness and professional information, 5) encourage them to develop a project of personal and professional life. Method: action research based on Thiollent (2008). 10 meetings were held where 13 subjects established interpersonal relationships through discussions, readings, group dynamics and reflected on the multiplicity of his career choice. The results showed that the educational intervention was effective, since most of the subjects could make your career choice, acquired the concept of work, and built a project of personal and professional life. We conclude that the teacher can contribute with their students in the same awareness on the concept of work, career choice and the ability of the study to get them to achieve higher goals in life.